2019
DOI: 10.1002/bjs5.50181
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre study of surgical referral and outcomes of patients with benign colorectal lesions

Abstract: BackgroundA multicentre cohort study was performed to analyse the motivations for surgical referral of patients with benign colorectal lesions, and to evaluate the endoscopic and pathological characteristics of these lesions as well as short‐term surgical outcomes.MethodsPatients who underwent surgery for a benign colorectal lesion in 15 Dutch hospitals between January 2014 and December 2017 were selected from the pathology registry. Lesions were defined as complex when at least one of the following features w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 36 publications
0
18
3
Order By: Relevance
“…However, 90 days mortality, which is a better marker for postoperative mortality, has not been used previously in screening literature (6,8,14,15,23). We also found that more patients could be treated with curative intent in the screened group, more could be treated with endoscopic resections, and that emergency surgery was almost eliminated in the screening group which is also new compared to other studies (8,(24)(25)(26). This is important as emergency treatment is associated with high mortality rates and morbidity rates (17,18,27), whereas endoscopic treatment is associated with lower mortality and morbidity compared with surgery (15,28).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…However, 90 days mortality, which is a better marker for postoperative mortality, has not been used previously in screening literature (6,8,14,15,23). We also found that more patients could be treated with curative intent in the screened group, more could be treated with endoscopic resections, and that emergency surgery was almost eliminated in the screening group which is also new compared to other studies (8,(24)(25)(26). This is important as emergency treatment is associated with high mortality rates and morbidity rates (17,18,27), whereas endoscopic treatment is associated with lower mortality and morbidity compared with surgery (15,28).…”
Section: Discussionmentioning
confidence: 52%
“…6,8,14,15,23 We also found that more patients could be treated with curative intent in the screened group, more could be treated with endoscopic resections, and that emergency surgery was almost eliminated in the screening group which is also new compared to other studies. 8,[24][25][26] This is important as emergency treatment is associated with high mortality rates and morbidity rates 17,18,27 , whereas endoscopic treatment is associated with lower mortality and morbidity compared with surgery. 15,28 The methodological limitations of this study include a setup that leaves room for selection bias and healthy user bias.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, we have evaluated the SMSA classification for the first time in the pT1 CRC confirming that it fairly discriminates which lesions are candidates for endoscopic resection. SMSA was first described by Gupta et al [26] and has confirmed in several studies its ability to identify which lesions are challenging [27,28]. In this sense, it is relevant to improve the resection skills of the endoscopists in order to evaluate which lesions are at risk of harboring an invasive CRC candidate for endoscopic resection and, in any case, obtain a complete endoscopic resection according to the characteristics of the lesion.…”
Section: Discussionmentioning
confidence: 97%
“…and clinical success rates for endoscopic resection were 87% (95% CI, 82-91) and 87% (95% CI, 80-92), respectively. Cumulative recurrence rates after 12 months were 22% (95% CI, 15-32) after piecemeal resection and 8% (95% CI, 2-22) after en-bloc resection, and adverse events occurred in 5% of cases (95% CI, [3][4][5][6][7][8][9]. The primary surgery referral rate for noninvasive LNPCPs was 7% (95% CI, 5-10).…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests there is still room for improvement regarding quality of endoscopic care for LNPCPs, because recurrence after EMR is significant, 6 compliance with surveillance guidelines is suboptimal, 7 and noninvasive LNPCPs are frequently referred for surgery. 8,9 Although expert centers have reported their outcomes of EMRs performed on LNPCPs, little is known regarding these outcomes in a screening setting. In this performance of 2 substudies, we evaluated the quality of endoscopic care for LNPCPs in the Dutch BCSP.…”
mentioning
confidence: 99%